Pengaruh Model Mind Mapping Terhadap Hasil Belajar PKn Siswa Kelas III SD - Yusiana Khoirun Nisa’; Moh Gufron (Universitas Negeri Malang, 2018)
Abstract: The aim of the study was to determine the effect of the Mind Mapping model on civic learning outcomes of third-grade elementary school students. Quasi-experimental method, with the nonequivalent design. The population of third-grade students of SDN 03 Jabalsari, IIIA as a control class of 15 students, and IIIB in the experimental class of 15 students. Mind Mapping treatment is given by the experimental group and conventional learning given the control class. The PKn learning outcomes of the experimental class students averaged 80.80 higher than the control class with a value of 64.27. The sig value (2-tailed) 0,000 <0,05 with a significance level of 5%. thing is 7,633 and table is 2,048. So that t count> t table 7,633> 2,048. It was concluded that there was the influence of the Mind Mapping model on the civic learning outcomes of third-grade elementary school students. Abstrak: Tujuan penelitian mengetahui pengaruh model Mind Mapping terhadap hasil belajar PKn siswa kelas III SD. Metode eksperimen semu, dengan rancangan nonequivalen. Populasi siswa kelas III SDN 03 Jabalsari, IIIA sebagai kelas kontrol 15 siswa, dan IIIB kelas eksperimen 15 siswa. Mind Mapping perlakuan diberikan kelompok eksperimen dan pembelajaran konvensional diberikan kelas kontrol. Hasil belajar PKn siswa kelas eksperimen rata–rata 80,80 lebih tinggi dari kelas kontrol dengan nilai 64,27. Nilai sig (2-tailed) 0,000<0,05 dengan taraf signifikasi 5%. thitung sebesar 7,633 dan ttabel sebesar 2,048. Sehingga thitung> ttabel 7,633 > 2,048. Disimpulkan ada pengaruh model Mind Mapping terhadap hasil belajar PKn siswa kelas III SD.